ʻUbaidallah ibn Buhtišuʻ on apparent death : the Kitab Taḥrīm dafn al-aḥyāʼ, Arabic edition and English translation - Ibn Bakhtīshūʻ, ʻUbayd Allāh ibn Jibrāʼīl. (Islamic Philosophy, Theology and Science. Texts and Studies, 2018)
The Kitāb Taḥrīm dafn al-aḥyāʾ , the Book on the Prohibition to Bury the Living , written by the Nestorian physician ʿUbaidallāh Ibn Buḫtīšūʿ (d. c. 1060 CE), deals with the causes, signs and treatments of apparent death. Based on a short pseudo-Galenic treatise, whose Greek original is lost, ʿUbaidallāh's Arabic commentary is a comprehensive and in many ways unique piece of scientific writing that moreover promotes a psychological understanding of physical illness. Oliver Kahl's present book offers a critical Arabic edition with annotated English translation of ʿUbaidallāh's work on apparent death, framed by a detailed introductory study and extensive glossaries covering all relevant terms; for comparative purposes, the Arabic and Hebrew recensions of the lost Greek prototype are presented in an appendix.